2012
DOI: 10.3961/jpmph.2012.45.4.219
|View full text |Cite
|
Sign up to set email alerts
|

Zolpidem Use and Risk of Fracture in Elderly Insomnia Patients

Abstract: ObjectivesTo evaluate the risk of fractures related with zolpidem in elderly insomnia patients.MethodsHealth claims data on the entire South Korean elderly population from January 2005 to June 2006 were extracted from the Health Insurance Review and Assessment Service database. We applied a case-crossover design. Cases were defined as insomnia patients who had a fracture diagnosis. We set the hazard period of 1 day length prior to the fracture date and four control periods of the same length at 5, 10, 15, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 26 publications
2
74
0
Order By: Relevance
“…Low-strength evidence showed that eszopiclone decreased wake time after sleep onset more than placebo, but there was substantial heterogeneity between trials (I 2 = 70%). Within the two 6-month trials, Walsh et al 109 reported greater improvement in wake time after sleep onset with eszopiclone compared with placebo (mean difference of 18 minutes) and Krystal et al 108 reported eszopiclone was not more effective than placebo. …”
Section: Sleep Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Low-strength evidence showed that eszopiclone decreased wake time after sleep onset more than placebo, but there was substantial heterogeneity between trials (I 2 = 70%). Within the two 6-month trials, Walsh et al 109 reported greater improvement in wake time after sleep onset with eszopiclone compared with placebo (mean difference of 18 minutes) and Krystal et al 108 reported eszopiclone was not more effective than placebo. …”
Section: Sleep Outcomesmentioning
confidence: 99%
“…108 Neither 6-month trial reported evidence of tolerance or withdrawal symptoms following discontinuation. 108,109 Specific adverse effects associated with eszopiclone use were somnolence (9% vs. 3% for placebo), unpleasant taste (23% vs. 3%), and myalgia (9% vs. 4%).…”
Section: Adverse Effectsmentioning
confidence: 99%
See 3 more Smart Citations